Habitat identity crisis caused by the riparian wetland squeeze in Tangon River Basin, Barind Region, India - Chakraborty, Rajsekhar; Talukdar, Swapan; Basu, Tithankar; Pal, Swades (Spatial information research (Online), 2018)
The present paper intends to delineate flood plain wetland in Tangon river basin (1988–2016) from Landsat images and to investigate the nature and causes behind squeezing wetland and losses. From the analysis it is found that the total recognized average wetland area in pre monsoon season and post monsoon season are respectively 13.37 and 67.05 km 2 in post dam period whereas in pre dam period it was 12.75 and 77.78 km 2 respectively. Flow reduction due to damming over Tangon in 1989 is one of the major causes behind squeezing wetland area. Agriculture extension replacing shallow and seasonal wetland, disconnection of discharge contributing Karatoya river form Tangon river, gradual disconnection with ground water column are the crucial reasons for growing wetland habitat quality. Inconsistent water supply, frequent drying up of wetland fringe area withstand against health of the wetland habitat. Considering the causes of habitat crisis, immediately agricultural extension reclaiming wetland should be stopped, ecological flow should be allowed from dam. These steps could minimize the growing habitat crisis in the study region.